An Overview on Transport Phenomena within Solid Electrolyte Interphase and Their Impact on the Performance and Durability of Lithium-Ion Batteries - Roberta Cappabianca; Paolo De Angelis; Matteo Fasano; Eliodoro Chiavazzo; Pietro Asinari (Energies, 2023)
The nature of the electrode–electrolyte interface has an impact on the performance and durability of lithium-ion batteries (LIBs). The initial electrolyte’s thermodynamic instability at the anode–electrolyte interface in LIBs results in the formation of a passivation layer, called solid electrolyte interphase (SEI). The initial dense and intact layer allows <semantics>Li+</semantics> transport and restricts electron tunneling, thus preventing electrolyte decomposition and ensuring the electrochemical stability of a battery. However, the growth of this layer can reduce the availability of active lithium and electrolyte, and ultimately lead to an irreversible battery capacity fade. Investigating the transport phenomena of lithium ions within SEI is crucial for understanding its formation and growth. Nonetheless, accurately describing all relevant mechanisms is challenging due to its complex and multiscale nature. An overview of current computational efforts to study <semantics>Li+</semantics> transport within SEI is given in this article, ranging from electronic/atomistic scale simulations to macroscopic models. The drawbacks and advantages of the proposed numerical approaches are summarized along with the obstacles that need to be overcome to obtain accurate experimental data, identified on the basis of the most recent literature evidence. We highlight collaboration gaps between modeling and experimental approaches, as well as the urgent need for new multiscale models, to gain a better understanding of such a crucial transport phenomenon.